AN ENHANCE APPROACH FOR DETECTING AND PREVENTING SINGLE AND COLLABORATIVE ATTACKS IN MOBILE AD-HOC NETWORKS - Sabo, Abdulrashid; Lawan, A. (FUDMA Journal of Sciences, 2023)
Mobile ad hoc network is a system of wireless mobile nodes that are dynamically self-organize in arbitrary and temporary topologies, with no fixed set of communication infrastructure and lack centralized administration, where network devices are inter-connected through wireless interface. Mobile nodes in Mobile ad-hoc Networks not only act as a host but as a router or relay stations for forwarding packets from source to destination. The dynamic nature and other characteristics of MANETs such as nodes mobility dynamic and topological changes makes it highly susceptible to various security attacks ranging from collaborative black hole/ gray hole attacks, sink hole attacks to eavesdropping attacks. The mentioned attacks mainly disrupt the routing process by giving false routing information in MANETs, thus finding safe routing path by avoiding malicious nodes is a genuine challenge. The research work aim at in cooperating RSA encryption algorithm to the cooperative bait detection scheme. The proposed work allow the source to use public key crypto system (in this case RSA) to encrypt data before transmitting it to the destination after the initial reverse tracing operations, it eliminate the used threshold value to indicate the reoccurrence of malicious nodes, it also eliminate the use of confirmation RREQ, since the public key cryptosystem introduced by the proposed work is sufficient enough to cover the transmitted data from an unknown attacker. The research work was simulated using network simulator tool NS2 and simulation results shows that the proposed works show an increase in packet delivery ratio, and a remarkable decrease